O ensino das terminologias biológicas através da aprendizagem significativa: proposta para a formação de professores - Maia, Dayse Peixoto (2009)
This research locates in the area of the Teaching of Sciences, including the teachers' formation and grew through the approach of the biological terminology, analyzed under it constituent genesis, articulate to the theoretical propositions of the Significant Learning, formation of scientific concepts, and communication aspects and language in classroom. It is treated of a research of qualitative orientation and it looked for through the observation, of the documental analysis of the text books and in questionnaires, the explanation of relevant possibilities to investigate as the Biological Terminologies are being approached by the teachers in their pedagogic practices, in the High School and which the linguistic support that the text books have been giving to teachers and students. Twelve schools, public and private, of High School of the city of Manaus and their teachers of Biology were part of the research. Theanalysis of the data was of empiric-interpretative nature. The obtained results demonstrate the ignorance of methodological theoretical aspects of the biological terminology on the part of teachers and students, the non appreciation of this theme in the courses of initial or continuous formation, as well as the superficial present terminological approach in the text books. Starting from such evidences a Strategy was elaborated of it Semantics Analyzes as base in the Theory of the Significant Learning, seeking to aid teachers in winning the pertinent difficulties to the morphology and semantics of the biological terms. This work opens perspectives for new researches about pedagogic application of the Biological terminology, as well as for analyses epistemológicas regarding the construction of the specialized lexicon of the Biology, among other possible unfoldings in the areas of the linguistics and of the communication regarding the teaching process and learning